Does the right to access to justice oblige the states to include a working court mandatory mediation system? - Greine, Elīna (Riga Graduate School of Law, 2023)
Over the last two decades mediation has become more popular. With the ongoing trend in Europe of making mediation mandatory there have been discussions about if the process of making mediation compulsory goes against the right to access to justice. And in order to ensure access to justice are states obliged to include mandatory mediation in their court systems. The aim of this work is to answer these questions and see how compulsory mediation has affected the access to justice. Results showed that the main aim of the Mediation Directive was not met and there is a need to introduce mandatory mediation to resolve it. Making the process compulsory does not go against the right, on the contrary it promotes it as proved by the results of the state analysis.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::European law; mediation; mandatory mediation; Article 6 of the ECHR; access to justice